Le contrôle judiciaire en droit britannique : justice naturelle ou “fairness” ? - Brown, L.; Bouchard, Mario (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1977)
Frequently in the past, attempts have been made to systematize the notion of judicial review of administrative action. Thus, the Donoughmore Commission proposed the judicial, quasi-judicial, purely administrative model of analysis. The Commission was severely criticized, especially after the implementation of certain recommendations of the Franks Report which, in improving the quality of the control exercised on administrative tribunals, underscored the ridiculous character of that existing in other fields. The most violent criticisms came certainly from Griffith and Street, and also from Professor Wade who denounced the progressive atrophy of natural justice, the latter being the main topic of the present article. That concept, distinguished from "procedural ultra vires" in that a judge may look beyond the law for rules he himself has set establishing certain procedural guarantees, goes back a long way in time. Nevertheless, it is not a panacea. Its scope is limited to the study of the means whereby a decision is reached; it does not examine the conclusion, but rather how that conclusion is determinded. The usefulness of the notion was diminished when a condition of its application, the duty to act judicially, was added. Ridge v. Baldwin put the pieces of the puzzle back into place by discarding the decisions which gave the concept a much too restrictive interpretation. These first steps of the fairness concept were rapidly followed in matters concerning the allocation of licences. Judicial intervention here dates back to the last century. Yet, the Nakkuda Ali and Parker decisions restrained the spread of control through an erroneous interpretation of an opinion by Lord Atkin. Both decisions were overturned by the Ridge case. Later on, it seems that Lord Denning took the lead in a movement aimed at extending the scope of the duty to act fairly. That principle received its modem da consecration in the Crockford's decision and was used later in other decisions of a like nature. The late professor de Smith remarked this new tendency to go beyond the words to see, in the matter at issue, what is fair and what is not. Domestic tribunals, not in union matters alone (Breen) but also in sports problems (Machin), have also had this obligation to act fairly imposed on them, even though, strictly speaking, they do not have judicial powers. The question is rather to know whether a legitimate expectation of the person involved in the decision is brought into play, although the extend of the obligation varies depending on the circumstances of the case. It would appear that there is continued refusal to intervene in matters of labour contracts when faced with a purely master and servant relation (Sylva). But now the complete absence of statutory guarantees is required (Malloch). Procedural guarantees have continued to evolve since then. More and more, in different areas, thanks to the initiative of judges like Lord Denning, a system of English administrative law has developed. The principle of the existence of more or less defined minimal procedural guarantees has been established, no matter whether the administrative act implies the exercise of judicial power or not. Yet, British courts still refuse to intervene in legislative functions, including regulations issuing from statutory committees, even should the legislative instrument result from false representations. Control over immigration matters has become increasingly tightened, even though, at one time, there was an apparent desire to sanctify the absolute character of the discretion exercised in that field. The widening ofthat control came about as much from legislative changes as from judicial decisions. Thus it is that in the Re H.K. decision, there was established the duty to act fairly on the part of an immigration officer who might wish to turn a person back at the border whom he considers to be inadmissible. Soon (if it has not already happened) Britons will also benefit from procedural guarantees in matters of land planning. A recent decision made use of the fairness concept in that field. English courts have undertaken to sanctify fundamental procedural guarantees. The name, the scope and the extent of these rules has varied and continues to vary. It would seem, however, that there is a desire to leave the categorization of the act of administration to one side in favour of dealing with the consequences of an act for the individual. If a decision touches an interest, an vested right, or a legitimate expectation, the citizen is entitled to have certain minimal procedural guarantees respected, which may vary according to the circumstances, but which always involve the determination of what is fair in the particular instance. It is a necessary adaptation to the new reality of administration, something we hope to see come about in the very near future in Canada.